STEAM TURBINE ISENTROPIC EFFICIENCY OF TC 663 MY 140 TYPE-UNIT 4 STEAM POWER PLANT CASE STUDY IN PT. PLN (PERSERO), BUKIT ASAM SECTOR, TANJUNG ENIM REGENCY, SOUTH SUMATERA PROVINCE - Puspawan, Angky (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2019)
Coal is one of the important natural resources that can produce energy for electricity generation. Bukit Asam Steam Power Plant (PLTU) PT. PLN (Persero) is a state-owned company that is in charge of managing coal into fuel to produce electricity through the Rankine cycle with one of its main tools being a steam turbine. Steam turbines function to convert heat energy from the boiler to mechanical energy to rotate the turbine. Because the heat energy has enough pressure, temperature, and flow of steam to rotate the turbine rotor. If a steam turbine is used continuously to reduce the quality and isentropic efficiency of the turbine. Therefore, it is necessary to do some work analysis on turbines type TC663 MY 140 Unit 4, Bukit Asam Sector PLTU. From observing and retrieving data and the results of calculating steam turbines during a two-day operation, the average value of isentropic efficiency on the first day was 57.86% with a range of 56.19% -59.92% and 54.51% on the second day 44.29% 59.58%.So,the pressure and temperature of the steam turbine greatly affect the performance of the steam turbine where if the pressure and the inlet temperature of the steam turbine are large then the work of the steam turbine increases and vice versa. From the results of calculations and discussion it can be concluded that the steam turbine used in PT. PLN (Persero) is still working well.